Aplicación de estrategia educativa en salud bucal denominada camaleón sonriente para niños/niñas con y sin discapacidad auditiva - Amézquita Peláez, Aura Dayane; Moscoso Giraldo, Scarleth Viviana; Unibio Salcedo, Ana Geraldine (Universidad Antonio Nariño, 2022)
To determine the effectiveness of the oral health education strategy called smiling chameleon take care of your teeth for school-age children with and without hearing impairment.